Proceedings of the 33rd Annual Conference on Design Automation Conference - DAC '96 1996
DOI: 10.1145/240518.240608
|View full text |Cite
|
Sign up to set email alerts
|

Module compaction in FPGA-based regular datapaths

Abstract: When relying on module generators to implement regular datapaths on FPGAs, the coarse granularity of FPGA cells can lead to area and delay inefficiencies. We present a method to alleviate these problems by compacting adjacent modules using structure extraction, local logic synthesis, and cell replacement. The regular datapath structure is exploited and preserved, achieving faster layouts after shorter tool run-times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Previous studies, [4] [7] [8] [9] [12] [13] [16], have shown that the logic density of FPGAs can be substantially increased by exploiting regularity at the placement, routing, and architecture levels. However, there are no extensive studies focusing on the effects of datapath synthesis on FPGA area.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies, [4] [7] [8] [9] [12] [13] [16], have shown that the logic density of FPGAs can be substantially increased by exploiting regularity at the placement, routing, and architecture levels. However, there are no extensive studies focusing on the effects of datapath synthesis on FPGA area.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are no extensive studies focusing on the effects of datapath synthesis on FPGA area. Existing datapath synthesis techniques can be roughly classified into four categories: regularity preserving logic transformations [10] [11], hard boundary hierarchical synthesis (synthesis that performs optimizations strictly within user-defined module boundaries), template mapping [5] [6] [14] [15], and module compaction [8] [9]. Among these four synthesis techniques, only regularity preserving logic transformations do not incur significant area overhead [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations